1997
DOI: 10.1111/j.1600-0404.1997.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of myocardial muscle functional parameters in patients with multiple sclerosis

Abstract: Structural and functional parameters of myocardium were evaluated with 2D+ Doppler echocardiography in two similar age groups of MS patients: S1: 12 subjects in 3-4 Degrees EDSS (Expanded Disability Status Scale), S2: 12 subjects in 5-7 degrees EDSS. The control group comprised 12 healthy subjects temporarily (at least 1 month) immobilized due to lower limb fractures. Investigations were performed in the supine position and 3 min after tilting to the erect position. Symptoms of organic myocardial injury which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…[34][35][36][37][38][39][40] The relationship between baseline disability and associated LV function in such patients remains unclear, as data are limited. Some studies have found no correlation between EDSS score and LV function, 35 whereas others have demonstrated impaired baseline LV function in MS patients with higher EDSS scores.…”
Section: Cardiac Rhythm Dysfunction: Ecg Changes and Arrhythmiasmentioning
confidence: 98%
See 1 more Smart Citation
“…[34][35][36][37][38][39][40] The relationship between baseline disability and associated LV function in such patients remains unclear, as data are limited. Some studies have found no correlation between EDSS score and LV function, 35 whereas others have demonstrated impaired baseline LV function in MS patients with higher EDSS scores.…”
Section: Cardiac Rhythm Dysfunction: Ecg Changes and Arrhythmiasmentioning
confidence: 98%
“…Some studies have found no correlation between EDSS score and LV function, 35 whereas others have demonstrated impaired baseline LV function in MS patients with higher EDSS scores. 36 There are several cases reported of young MS patients with low EDSS who developed severe acute LV dysfunction, and recovered rapidly after steroid therapy. 20,37,38 Although some of the cases described involved both LV dysfunction and accompanying pulmonary edema, other cases involve isolated pulmonary edema.…”
Section: Cardiac Rhythm Dysfunction: Ecg Changes and Arrhythmiasmentioning
confidence: 98%
“…Exceptionally, atrial fibrillation (Chagnac et al ., 1986) or acute pulmonary oedema (Gentiloni et al ., 1992; Melin et al ., 1996) has been reported, but these conditions appear to be related to acute brainstem lesions. Only one study (Ziaber et al ., 1997) has reported assessment of cardiac function by transthoracic two‐dimensional Doppler echocardiography, which showed decreased left ventricular ejection fraction (VEF) in MS patients with a high Expanded Disability Status Scale (EDSS) score (5–7) (Kurtzke, 1983). However, this study was based on ultrasonography and limited to left ventricular function.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding functional parameters, most changes were detected in respect to LV EF. This corresponds to former reports using 2D-echocardiography [17], which demonstrated in severely disabled MS patients a decrease of LV EF that. Changes of LV EF were detected in 4/15 patients, all of them showed also decreased concentrations of PCr.…”
Section: Mri: Methology Findings and Correlation To Mrs Resultsmentioning
confidence: 46%
“…Available epidemiologic data are controversial: whereas patients with multiple sclerosis have been reported to have an increased risk of cardiovasular death when compared to an age matched control group [15], others find a significantly reduced comorbidity of acute myocardial infarction, heart failure, hypertension, angina pectoris, cerebrovascular disease in MS patients who were 65 years and older [16]. Additionally, disease related decreased physical mobility and activity may have an impact on cardiac function [17]. Although currently there is no consensus whether MS inherently affects the heart, putative MS autoantigens like a B crystalline and S 100b are either constitutively expressed in the heart or inducible [3,4].…”
Section: Cardiac Disease In Msmentioning
confidence: 99%